Medical humanities, sociology and the suffering self : surviving health - Lowe, Wendy (Lecturerer in medical sociology) (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Following criticisms of the traditionally polarized view of understanding suffering through either medicine or social justice, Lowe argues that medical humanities can help to go beyond the traditional biographical and epistemic breaks to see into the nature and properties of suffering and what is at stake"--
Stitching suffering together -- Patterns of suffering -- Suffering as foundational to health professional education -- Sorting the wood from the trees -- The suffering self and burning woman -- Pilgrimages -- how can medical humanities think differently about suffering? -- Diving Down Deep.
OCLC-licensed vendor bibliographic record.
Keywords: Medicine and the humanities; Suffering